Carnation in protected cultivation is a goldmine - Raj, Desh (Indian Horticulture, 2019)
Carnation cultivation in Himachal Pradesh has proven a very profitable venture to growers as is an evident from the fact that acreage under carnation has increased from 3 ha in 1993 to 59 ha in 2012. Growers produce 5.75 crore cut flower stems of over `14.35 crore (2012). Globally over 500 million US cut flowers of carnation are sold through United Nations common trade (2011).